Creating the next steps to care: Maternal heath, improvisation, and Fulani women in Niamey, Niger. Issue 3 (1st September 2016) - Burgess, Sarah
ABSTRACT: On paper, Niger's maternal healthcare system is extensively outlined by policies which assure access to certain services and create hierarchical referral chains. In practice it remains intensely improvisational: actors in the system must frequently make up the next steps to giving and receiving care, often outside the existing policies and procedures. Although population health in Niger has improved since the recently enacted gratuité des soins policy (which guarantees free access to certain material and child health services), care on the ground is still dictated by difficult circumstances and scarce resources. Health workers often lack the required medications and supplies; nevertheless, they must find ways to deliver services. Patients seeking maternal health services are frequently dissatisfied with the care they receive and so move forward of their own volition, by negotiating with health workers or by looking for services elsewhere. This research builds on recent scholarly work on improvisation, and asks us to further look at the ways that improvisation can be informed by the identity of the actors. Examining case studies of women from the Fulani ethnic group illustrates how particular cultural differences can inform improvisation. Analysing improvisation can also have policy implications; identifying typical points of departure from the official maternal health care system can reveal points where Niger can bolster its commitment to a universally high quality of care.